Cross-immunity against SARS-COV-2 variants of concern in naturally infected critically ill COVID-19 patients. Issue 1 (January 2023) - Fraser, Douglas D.; Patel, Maitray A.; Van Nynatten, Logan R.; Martin, Claudio; Seney, Shannon L.; Miller, Michael R.; Daley, Mark; Slessarev, Marat; Cepinskas, Gediminas; Juneja, Ganeem K.; Sabourin, Vanessa; Fox-Robichaud, Alison; et al.
Abstract: Critically ill patients infected with SARS-CoV-2 display adaptive immunity, but it is unknown if they develop cross-reactivity to variants of concern (VOCs). We profiled cross-immunity against SARS-CoV-2 VOCs in naturally infected, non-vaccinated, critically ill COVID-19 patients. Wave-1 patients (wild-type infection) were similar in demographics to Wave-3 patients (wild-type/alpha infection), but Wave-3 patients had higher illness severity. Wave-1 patients developed increasing neutralizing antibodies to all variants, as did patients during Wave-3. Wave-3 patients, when compared to Wave-1, developed more robust antibody responses, particularly for wild-type, alpha, beta and delta variants. Within Wave-3, neutralizing antibodies were significantly less to beta and gamma VOCs, as compared to wild-type, alpha and delta. Patients previously diagnosed with cancer or chronic obstructive pulmonary disease had significantly fewer neutralizing antibodies. Naturally infected ICU patients developed adaptive responses to all VOCs, with greater responses in those patients more likely to be infected with the alpha variant, versus wild-type.